MENELUSURI PENDIDIKAN ISLAM PADA ERA KEPEMIMPINAN KHULAFAUR RASYIDIN - Eka Dwi Ningsih; Ahmadi Ahmadi (JOURNAL SAINS STUDENT RESEARCH, 2025)
This research aims to examine Islamic education during the Khulafaur Rasyidin period, which includes the reign of Abu Bakar, Umar bin Khattab, Uthman bin Affan, and Ali bin Abi Talib. The main focus of this research is to understand the objectives of Islamic education, Islamic education curriculum, learning methods, educational materials, teaching staff, and educational institutions applied during this period. The method used in this research is library research, namely research whose studies are carried out by tracing and examining literature or written sources related to the subject matter. The results show that although there are differences in the focus and application of education in each period of leadership, the objectives of Islamic education remain consistent in strengthening the faith and teaching the principles of Islamic muamalah. The curriculum covered various aspects, including religious education, practical skills and language. The learning methods used involved lectures, memorization, discussions, as well as practical exercises. Educators during this period were highly valued, with many companions serving as teachers. Educational institutions, such as Kutabs and mosques, developed according to the needs of the people at that time. Overall, Islamic education during the time of the Khulafaur Rashidin flourished, although there were obstacles due to the unstable political situation in some reigns.